Reescritura de Ensaio sobre a cegueira ao cinema: ressignificações das imagens - Alves, Renata da Costa (2012)
This dissertation proposes, through the analysis of the novel Ensaio sobre a cegueira (1995), by Jose Saramago and its filmic rewriting (2008), by Fernando Meirelles, to investigate translation strategies, delineating mainly how images of the literary text (the blindness, the abjection, the chaos, the solidarity, and the plot itself) were rewritten in the cinematographic language, creating, this way, new images of the literary universe for new audiences. In order to do so, we seek to understand the way converging and diverging features in relation to the two works contribute to give both the novel and the movie a singular aspect, considering the particularities of each language (literature and cinema). First, we will reflect on translation studies, since some of their principles give support to ideas followed in this research, as the concept of rewriting by André Lefevere (1992). Afterwards, some questions on the construction of Saramago’s narrative project will be focused on. Allegory will be analyzed as a literary device used to resignify the images of the “white blindness” – the leitmotif of the narrative. It will be also taken into account internal and external elements of the plot, such as the analysis of characters, and the context of production and reception in which the novel was written. Finally, it will be analyzed the filmic rewriting of the literary work, presenting some translation strategies used by the director in his composition, as well as aspects of the poetics of the film and its intertextualities. The results show that the filmic text by the Brazilian director was not in the shade of the novel by the Portuguese author, given that the film got a particular characteristic, constrained by cultural, ideological, semiotic and authorial issues. Being the movie a new fictional work, it is also a new reflection on the value of each human being inside the collective entity called society.